Застосування поверхневих хвиль для вивчення характеристик газочутливих сенсорiв на поверхнi твердого тiла - Klochko, M. S.; Syrkin, E. S.; Voinova, M. V. (Publishing house "Academperiodika", 2018)
Dispersion relations for surface waves and attenuation parameters in a crystal with the impurity monolayer adsorbed on its top are studied. We consider a face-centered cubic crystal with central interaction between the nearest neighbors as a model and calculate the value of m*0 for the adsorbed surface monolayer. Beginning from it (m0 < m*0), the surface wave splits off the upper edge of the volume spectrum and attenuates non-monotonously (with oscillations), when penetrating into the crystal bulk.